Edukasi Teknologi Akuntansi: Penerapan ERP Odoo dalam Pengembangan Kompetensi Lanjutan Pada Siswa di SMK BOASH 1 Bogor - Amelia Oktrivina; Indah Masri; Yetty Murni; Salis Musta ‘Ani; Shanti Lysandra; Sailendra Sailendra; Agung Terminanto; Calya Sekar Arum Pitaloka; Miranda Alifarahmah Juwanto (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2026)
This Community Service (PKM) activity aims to provide accounting technology education through the implementation of the Odoo Enterprise Resource Planning (ERP) system to improve the advanced competencies of students at SMK Boash 1 (SMK Taruna Terpadu 1) Bogor. The training was held on August 26, 2025, for three hours, involving 31 12th-grade students and two accompanying teachers. The implementation method included an introduction to the accounting module in Odoo, practical simulations, and evaluation through a participant satisfaction survey. The results of the activity demonstrated an increased understanding of the ERP system and its application in digital accounting. This activity also produced outputs in the form of IPR (Intellectual Property Rights) number 000986082 and activity documentation. Thus, this training successfully contributed to preparing competent human resources ready to face the challenges of the Industry 4.0 era.